Implementation Dynamics of Mangrove Ecotourism Governance in Tanjungpinang Coastal Area: A Grindle-Based Analysis - Fatmo, Siyardi; Samin, Rumzi; Akhyary, Edy; Septiawan, Armauliza; Subiyakto, Rudi (Indonesian Tourism Journal, 2025)
Ecotourism has emerged as a key strategy for harmonizing environmental conservation with local economic development, particularly in biodiverse coastal regions. Mangrove forests, as critical ecological buffers and carbon sinks, have gained attention for their potential to support sustainable tourism models. This study investigates the dynamics of policy implementation for mangrove ecotourism in the coastal area of Tanjungpinang, Indonesia, using Grindle’s Policy Implementation Framework to analyze both policy content and implementation context. The research aims to evaluate how the local tourism policy specifically Regional Regulation No. 8 of 2021 is translated into action at the grassroots level. A qualitative descriptive method was employed, incorporating in-depth interviews, field observations, and document analysis involving various stakeholders, including government agencies, NGOs, tourism operators, and community representatives. Findings reveal that while the regulation outlines clear environmental and socio-economic goals, implementation is hindered by inter-agency fragmentation, centralized decision-making, limited infrastructure, and minimal community participation. Power asymmetries and bureaucratic misalignment further complicate the delivery of intended outcomes. Despite these obstacles, some benefits have emerged, such as increased awareness and pilot ecotourism initiatives. The study concludes that for mangrove ecotourism to achieve meaningful ecological and economic outcomes, a participatory governance model is essential. Strengthening institutional coordination, enhancing grassroots involvement, and securing diversified resources are critical to bridging the gap between policy vision and practical impact.